Proventricular dilatation disease (PDD) and megaesophagus in a blue-fronted Amazon parrot (Amazona aestiva) - case report. - Marietto-Goncalves, Guilherme Augusto; Zampoli Troncarelli, Marcella; Lopes Sequeira, Julio; Andreatti Filho, Raphael Lucio (My University, 2009)
The present article relates the occurrence of Proventricular Dilatation Disease (PDD) in a 20 years old blue-fronted amazon parrot (Amazona aestiva). The bird was raised in captivity and was examined at the Ornitopathology Laboratory of São Paulo State University's Veterinarian Hospital, São Paulo State, Brazil. The parrot clinically presented regurgitation, tremors and dyspnea. This is the first case of PDD followed by megaesophagus in a blue-fronted amazon parrot (A. aestiva). This pathological case was not described in birds at all.